Community-Based Disaster Mitigation System In Muncar Beach, Banyuwangi Regency - Moh. Fahrurrozi; Marta Ishardhi (Journal of Aquaculture Science, 2021)
Muncar Beach, Banyuwangi Regency is an area with high disaster risk. Community-based disaster management will be much more effective than formal agencies set up by the state. But it also does not mean that formal institutions are not important. Education, counseling, and public awareness are non-structural/non-physical disaster mitigation activities. This study aims to analyze the level of knowledge and preparedness of coastal communities in Muncar, Banyuwangi Regency in dealing with disasters, and to find out how the community-based disaster mitigation system in Muncar Beach, Banyuwangi Regency is. This research uses qualitative methods with qualitative descriptive research. Data were obtained through observation, in-depth interviews, and documents. The subjects of this research are community leaders, fishermen, and the people of Kedungrejo Muncar Village. The analysis technique in this research is inductive. In this study, the inductive analysis used is an interactive analysis technique. The results show that the paradigm of disaster management at the population level has not changed much and is still associated with myths. Knowledge and awareness of coastal communities about disaster mitigation are still very low. Keywords: Mitigation, Disaster, Muncar, Banyuwangi